Dynamic model of different configurations of stabilization pound systems - Ochoa, María Paz (2014)
In this work different configurations of stabilization ponds are con-sidered. Dynamic modeling of each pond was implemented within a dynamic optimization environment and the whole system was simulated during a time horizon of four months. A detailed mechanistic model is constructed, based on first principles of mass conservation, of different types of systems of anaerobic, aerobic and facultative ponds in series in order to compare their performance. Model takes into account dynamic mass balances of biomass of algae, the main groups of bacteria: heterotrophic bacteria, autotrophic bacteria, fermenting bac-teria, acetotrophic sulphate reducing bacteria and acetotrophic methanogenic bacteria. Also, mass balances for organic load were formulated, such as slowly biodegradable particulate COD (Xs), inert particulate COD (XI), fermentation products (SA), inert soluble COD (SI), and fermentable readily biodegradable soluble COD (SF). For nutrients, ammonium and ammonia nitrogen (NH), ni-trate and nitrite nitrogen (NO), sulphate sulphur (SO4) and dissolved oxygen (DO). Finally, molecular nitrogen (N2) and methane (CH4) emissions were con-sidered in the model. For the whole time horizon, we find that the conventional configuration is better than the actual configuration of the wastewater treatment plant. Even though the differences are not as high as expected, this fact influences the total energy con-sumption by the aerators of the aerobic ponds.